Bending resistance of partially encased beams at high temperatures: three dimensional numerical simulation - Piloto, P.A.G. (2018)
Partially Encased Beams (PEB) are composite steel and concrete elements in which the web of the steel section is encased by reinforced concrete. The experimental investigation was already developed under fire and under elevated temperatures by Paulo Piloto et al. The bending resistance of partially encased beams submitted to three bending point loading condition, at four temperature levels (20, 200, 400 and 600 ºC) is determined, based on the three dimensional finite element model (steel profile, reinforcement, stirrups and concrete). An incremental and iterative (arc length) solution method is defined to solve a geometric and material non-linear analysis (ANSYS), using a reduced integration method. The model considers perfect contact between steel and concrete. The material model assumes plasticity. The initial imperfection mode is based on the elastic stability solution (ANSYS). Two types of stirrups were considered: welded to the web (PEBA) and welded to the flanges (PEBB), three different lengths (2.5, 4.0 and 5.5 m) and three types of cross section dimensions were simulated, based on the dimensions of different classes of steel profiles (IPE100, IPE200 and IPE300). A total of 72 models were simulated, showing conservative results with respect to the simple calculation method of EN1994-1-2. The bending resistance of the numerical results was determined for multiple force events, The proportional limit force (Fp) with respect to the vertical displacement, the force (Fy) resulting from the intersection method between two straight lines drawn from linear and non-linear interaction of the vertical displacement; the load event for the vertical displacement limit of L/30 (FL/30); and the maximum load level for the asymptotic behaviour of lateral displacement (Fu). Results are in accordance to the new formula presented by Vila Real et al. and adapted to composite section.